The use of multiple hypothesis-generating methods in an outbreak investigation of Escherichia coli O121 infections associated with wheat flour, Canada 2016–2017. (7th October 2020) - Morton, V.; Kershaw, T.; Kearney, A.; Taylor, M.; Galanis, E.; Mah, V.; Adhikari, B.; Whitfield, Y.; Duchesne, C.; Hoang, L.; Chui, L.; Grant, K.; et al.
Abstract: A Canadian outbreak investigation into a cluster of Escherichia coli O121 was initiated in late 2016. When initial interviews using a closed-ended hypothesis-generating questionnaire did not point to a common source, cases were centrally re-interviewed using an open-ended approach. The open-ended interviews led cases to describe exposures with greater specificity, as well as food preparation activities. Data collected supported hypothesis generation, particularly with respect to flour exposures. In March 2017, an open sample of Brand X flour from a case home, and a closed sample collected at retail of the same brand and production date, tested positive for the outbreak strain of E. coli O121. In total, 76% (16/21) of cases reported that they used or probably used Brand X flour or that it was used or probably was used in the home during their exposure period. Crucial hypothesis-generating techniques used during the course of the investigation included a centralised open-ended interviewing approach and product sampling from case homes. This was the first outbreak investigation in Canada to identify flour as the source of infection.